2016
DOI: 10.1080/02723638.2016.1206700
|View full text |Cite
|
Sign up to set email alerts
|

Affective neighbourly relations between migrant and local residents in Shanghai

Abstract: In urban China there is growing scholarly interest in neighbourhood social interaction, but most studies focus on overt neighbouring activities whilst less is known about the affective dimension of neighbourhood relations, such as mutual trust and care. By surveying 1,420 residents from Shanghai, this study examines the affective relationship between rural migrants and local urban neighbours and explores whether the frequency of neighbouring and contextual characteristics may affect this outcome. Our results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 51 publications
3
32
3
Order By: Relevance
“…As an important upstream-level community intervention to minimize health disparities, it is important to optimize the density and mix of local-to-migrant housing to promote a sense of community and enhance people’s social capital and wellbeing [ 69 ]. Provisioning access to key community services is also significant; for instance, with the evidence confirming the environment injustice and inefficient access to public parks in Shanghai [ 70 , 71 , 72 , 73 ], the local government should aim to improve the quality of green services to provide a livable and inclusive environment promoting mental health of the migrant workers and hence enhancing the overall mental capital of the city. At an institutional level, policy makers have a role to further refine policies related to hukou registration with a view to improve access to basic services (reduce their disparities) that adversely affect migrant workers’ mental health.…”
Section: Discussionmentioning
confidence: 99%
“…As an important upstream-level community intervention to minimize health disparities, it is important to optimize the density and mix of local-to-migrant housing to promote a sense of community and enhance people’s social capital and wellbeing [ 69 ]. Provisioning access to key community services is also significant; for instance, with the evidence confirming the environment injustice and inefficient access to public parks in Shanghai [ 70 , 71 , 72 , 73 ], the local government should aim to improve the quality of green services to provide a livable and inclusive environment promoting mental health of the migrant workers and hence enhancing the overall mental capital of the city. At an institutional level, policy makers have a role to further refine policies related to hukou registration with a view to improve access to basic services (reduce their disparities) that adversely affect migrant workers’ mental health.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Wu and Logan (2016) find that migrants are more prone than local residents towards neighbouring practices. In particular, interactions with local residents are conducive to mutual feelings of care, trust and friendship within communities (Wang, Zhang, and Wu 2017b).…”
Section: Social Network and Communitiesmentioning
confidence: 99%
“…Indeed, in Chinese commodity neighbourhoods, collaboration amongst residents is often necessary in order to fight against poor estate management (Lu et al, 2018;He, 2015). However, despite the decline of manifest neighbouring in commodity housing estates, such as visiting each other's homes, recent research has also found that latent neighbouring remains at a high level in virtually all neighbourhood types (Wang et al, 2017c, Lu et al, 2018.…”
Section: Neighbouring and Community Participation In Chinese Citiesmentioning
confidence: 99%
“…Additionally, Wang et al (2017c) found that there is a large portion of commodity residents who believe that residents are taking good care of each other and consider their neighbours as trustworthy. Recent studies also find that neighbouring is an important form of social networking for rural migrants (Liu et al, 2017a;Liu et al, 2017b;Wu & Logan, 2016).…”
Section: Neighbouring and Community Participation In Chinese Citiesmentioning
confidence: 99%
See 1 more Smart Citation